The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1039/d3dt03418f
|View full text |Cite
|
Sign up to set email alerts
|

In situ sonochemical synthesis of flower-like N-graphyne/BiOCl0.5Br0.5 microspheres for efficient removal of levofloxacin

Shuyan Li,
Mingxuan Sun,
Xiangzhi Huang
et al.

Abstract: A series of flower-like N-graphyne/BiOCl0.5Br0.5 microspheres are constructed through an in situ sonochemical synthesis method. The improved adsorption and photocatalytic performance for the removal of levofloxacin are verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…50 The weak peak at 395.7 cm −1 of BiOCl could be assigned to the B 1g and E g band generated by the motion of oxygen atoms. 51…”
Section: Resultsmentioning
confidence: 99%
“…50 The weak peak at 395.7 cm −1 of BiOCl could be assigned to the B 1g and E g band generated by the motion of oxygen atoms. 51…”
Section: Resultsmentioning
confidence: 99%
“…With the development of society, the demand for high-performance energy materials is increasing. Owing to the wide application in photoelectrocatalysis, biosensors, supercapacitors, and so on, the preparation of TiO 2 has been a research hot spot for a long time. , Owing to the optical, structured, and electronic advantages, nanostructured TiO 2 -based photoelectrodes are promising for application as photoelectrochemical (PEC) devices, and photoelectrodes based on nanowire, nanorod, and nanoparticle structure have been widely studied. Nowadays, many researchers focus on the catalysts, such as TiO 2 /Ti 3 C 2 , Bi/BiOBr, and N-graphyne/BiOCl 0.5 Br 0.5 , but a few focus on its carrier. However, the photoelectrochemical properties of anodic TiO 2 nanotubes (ATNTs), one of its important carriers, have been studied less. It is worth mentioning that the ATNT array is usually formed in the electrolyte containing halogen ions typically, whereas the dense film in the electrolyte without halogen ions. Some researchers attributed the formation of porous film to an electrochemical dissolution reaction (i.e., TiO 2 + 6F – + 4H + → [TiF 6 ] 2– + 2H 2 O), and some other researchers suggested that the mechanism of porous film formation is related to the contamination layer formed by halogen ions. In summary, all of these studies supported the conclusion that the anion is indispensable for the formation of anodic TiO 2 nanotubes. Unlike other forms of TiO 2 , ATNT arrays may have defects in strength due to corrosion by fluoride ions during rapid growth. Therefore, it is crucial to slow down or prevent the corrosion of fluoride ions on the nanostructure during anodization to improve the stability of the nanotube array performance.…”
Section: Introductionmentioning
confidence: 99%
“…12–14 The key to the photocatalytic degradation of antibiotics is the selection of photocatalysts, especially the development of new photocatalysts that can degrade antibiotics under visible light conditions. 15–24 Copper aluminate (CuAl 2 O 4 , CAO) is a commonly used photocatalyst because of its high charge transfer and separation efficiency, high thermal and chemical stability, environmental friendliness and other advantages, and it is widely used to degrade dyes, antibiotics and other pollutants that are difficult to degrade naturally. 25–28 Interestingly, the combination of other excellent semiconductor materials with CAO can greatly enhance the electron and hole transfer and separation efficiency of a system, thus enhancing the photocatalytic activity of the system.…”
Section: Introductionmentioning
confidence: 99%